THE CHALLENGES AND STRATEGIES OF STORING LARGE VOLUMES OF DATA IN THE MODERN WORLD - Deineka, Oleg; Harasymchuk, Oleh (Ukrainian Information Security Research Journal, 2023)
In the modern world, the storage of large volumes of data is becoming an extremely relevant issue. Consumers and organizations continually generate large amounts of information, and this trend is on the rise. To ensure efficient and secure storage of this data, it is important to consider the challenges and strategies used in this field. A global trend in data storage is the expansion of information access capabilities. Organizations actively implement various types of access, such as cloud solutions, virtualization, and distributed storage systems. This enables greater availability and speed of data retrieval, which is crucial in today's industrial environment. Organizations must adhere to existing security standards and regulations to ensure the confidentiality, integrity, and availability of information. This means that they need to establish proper procedures, controls, and monitoring to protect data from unauthorized access and other threats. The volumes of information will continue to grow, and along with that, the importance of ensuring the security and transparency of its storage will increase. Developing new strategies and technologies to achieve this will be a significant task for the data storage industry in the future.